Electric power systems resiliency modelling, opportunity and challenges - Bansal, Ramesh C.; Mishra, Manohar; Sood, Yog Raj (Elsevier, AP, Academic Press, 2022)
Electric Power Systems Resiliency: Modelling, Opportunity and Challenges considers current strengths and weaknesses of various applications and provides engineers with different dimensions of flexible applications to illustrate their use in the solution of power system improvement. Detailing advanced methodologies to improve resiliency and describing resilient-oriented power system protection and control techniques, this reference offers a deep study on the electrical power system through the lens of resiliency that ultimately provides a flexible framework for cost-benefit analysis to improve power system durability.Aimed at researchers exploring the significance of smart monitoring, protecting and controlling of power systems, this book is useful for those working in the domain of power system control and protection (PSOP).- Features advanced methodologies for improving electrical power system resiliency for different architectures, e.g., smart grid, microgrid and macro grid- Discusses resiliency in power generation, transmission and distribution comprehensively throughout- Includes case studies that illustrate the applications of resilience in power systems